CURRENT GENERAL CONDITIONS OF SPORTS AND TOURISM - Spasoje Bjelica; Šemsudin Džeko (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
In order to determine social conditions of an area, mostly inhibited by members of this group, it is primarily essential to indicate general conditions which arise and in which these activities related to sports and tourism occur. These general activities are, on a large scale, infl uenced by common, world trends, among which globalization cannot be bypassed. The area populated by the majority of the group is specifi c due to change of the property relations, as well as the social structure. In that regard, we need to contribute to prevention or reduction of negative and slow development as much as possible, on the other hand, give incentive to the positive and progressive one.